PERSEPSI PENGUNJUNG TERHADAP KEGIATAN WISATA DI TAMAN KUPU-KUPU GITA PERSADA - Putri Dwi Mei Kartini; Gunardi Djoko Winarno; Dian Iswandaru; Agus Setiawan (Jurnal Hutan Tropis, 2021)
One of the tourist destinations in Wan Abdul Rachman Forest Park in Lampung, which has a variety of butterflies, namely the Gita Persada Butterfly Park. Research development needs to be done so that this park gives visitors satisfaction and the sustainability of butterflies. This study aims to study how visitors perceive tourism activities. The method used through direct observation and closed interviews containing questionnaires with aspects of assessment of facilities and shuttles, accommodation, infrastructure and tourist attractions. The data obtained were analyzed using One Score One Indicator and analyzed using a Likert Scale. The results of the study show that the facilitation and service aspects, as well as infrastructure, are classified as normal, while the tourist objects are classified as good. Visitors' perceptions stated that repairs should be made to the parking area, construction of counters, gift shops, information signs, tourgues, camping ground, homestays, tree houses and photo booths.